Zealantha thorpei gen. et sp. nov. (Diptera: Anthomyzidae), first family representative from New Zealand - Roháñek, Jindãich (Zootaxa, 2007)
The first representative of the family Anthomyzidae discovered in New Zealand, viz. Zealantha thorpei sp. nov., is described and illustrated. Zealantha gen. nov. is diagnosed and its relationship to other known genera of Anthomyzidae is discussed on the basis of morphological features including characters of the male and female internal genitalia. Notes on the habitat association and distribution of the new species are given.